Comparison Of Mechanical, Physical And Thermaproperties Of Conventional Plastics Fabricated Using 3D Printing And Injection Moulding - Thajudin, Nuur Laila Najwa (Universiti Sains Malaysia, 2018)
In this study mechanical, physical and thermal properties of products fabricated through Fused Deposition Modelling (FDM) 3D printing were compared with products manufactured using conventional plastic processing equipment, injection moulding. In order to check the efficiency and consistency of both fabrication methods, therefore different types of plastics wasinvestigated, namely, acrylonitrile butadiene styrene (ABS), polylactic acid (PLA) and nylon 6 (PA6). Tensile properties and impact strength was measured through Universal Testing Machine and Impact Tester Machine respectively. The thermal properties were determined by Thermal Gravimetric Analysis (TGA) which measure the thermal stability for each type of plastic fabricated with FDM 3D printing and injection moulding. SEM analysis was carried out using Hitachi TM3000 Scanning Electron Microscopy to observe the presence of voids and pores in the samples for different fabrication method. Water absorption for printed and injected samples was carried out according to ASTM D570 at room temperature for 24 hours using distilled water. The density of each fabricated plastics were determined using density balance at room temperature. Viscosity test was carried out for each different fabricated samples in measuring the viscosity using Cannon Ubberlohde Viscometer no.1. Tensile strength, elongation at break, Young’s modulus and impact strength was found to be higher for samples fabricated using injection moulding compared FDM 3D printed sample with percentage difference of 39.7%, 41.8%, 26.9% and 60.9%, respectively. Density and water absorbed by injected samples were found higher compared FDM 3D printed samples by 8.4% and 51.6%. Crystallinity, thermal stability and viscosity related to molecular distribution between injected and FDM printed samples were found comparable.